2007
DOI: 10.1523/jneurosci.5100-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Release Generates a Tonic GABAAReceptor-Mediated Conductance That Modulates Burst Precision in Thalamic Relay Neurons

Abstract: Tonic inhibition has emerged as a key regulator of neuronal excitability in the CNS. Thalamic relay neurons of the dorsal lateral geniculate nucleus (dLGN) exhibit a tonic GABA A receptor (GABA A R)-mediated conductance that is correlated with ␦-subunit expression. Indeed, consistent with the absence of ␦-subunit expression, no tonic conductance is found in the adjacent ventral LGN. We show that, in contrast to the situation in cerebellar granule cells, thalamic ␦-subunit-containing GABA A Rs (␦-GABA A Rs) do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 48 publications
15
98
0
1
Order By: Relevance
“…Synaptic spillover from action potential-dependent vesicular release of neurotransmitter is thought to be a primary source for the ambient GABA responsible for activating extrasynaptic tonic GABA A receptors (Brickley et al, 1996;Wall and Usowicz, 1997;Bright et al, 2007). In agreement with these findings, application of a sodium channel blocker mimicked the results obtained by BIC application (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Synaptic spillover from action potential-dependent vesicular release of neurotransmitter is thought to be a primary source for the ambient GABA responsible for activating extrasynaptic tonic GABA A receptors (Brickley et al, 1996;Wall and Usowicz, 1997;Bright et al, 2007). In agreement with these findings, application of a sodium channel blocker mimicked the results obtained by BIC application (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Subunit composition also appears to be specific to both the brain subregion and cellular subtype of the neurons on which they are located. For example, extrasynaptic GABA A receptors containing the ␦ subunit have been shown to mediate tonic inhibition in cerebellar granule cells (for review, see Farrant and Nusser, 2005), dentate gyrus granule cells (Wei et al, 2003), hippocampal interneurons (Semyanov et al, 2003;, and thalamocortical projection neurons (Belelli et al, 2005;Cope et al, 2005;Jia et al, 2005;Bright et al, 2007). Although immunohistochemical studies of GABA A receptor subunit expression have been limited to the rat, these studies have demonstrated diffuse expression patterns of the ␦ subunit in the striatum (Pirker et al, 2000;Schwarzer et al, 2001).…”
Section: Extrasynaptic Gaba a Receptors In Msnsmentioning
confidence: 99%
“…It is apparent that tonic inhibition is essential for dynamically regulating the neuronal output, frequency of firing, and gain control of neurotransmission (12)(13)(14)(15)(16)(17)(18)(19). In addition, extrasynaptic GABA A Rs have been further shown to be targets for a wide range of endogenous and pharmacological agents, such as neurosteroids, anesthetics, ethanol, and anticonvulsants (20 -23).…”
Section: ␥-Aminobutyric Acid Type a Receptors (Gaba A Rs)mentioning
confidence: 99%
“…In addition, a tonic form of inhibition in thalamocortical relay neurons is generated via persistent activation of extrasynaptic ␣ 4 ␤ 2 ␦ receptors (Porcello et al, 2003;Belelli et al, 2005;Cope et al, 2005;Jia et al, 2005Jia et al, , 2008Chandra et al, 2006;Bright et al, 2007;Peden et al, 2008). In the present study, we compared the actions of eszopiclone and zolpidem on these three populations of GABA A -Rs in the mouse thalamus.…”
mentioning
confidence: 99%